Effects of the AlN nucleation layer thickness on the crystal structures of an AlN epilayer grown on the 6H-SiC substrate. Issue 14 (18th July 2019) - Arslan, Engin; Öztürk, Mustafa K.; Özçelik, Süleyman; Özbay, Ekmel
ABSTRACT: The influence of the LT-AlN(NL) growth times on the mosaic structure parameters of the AlN layer grown on the LT-AlN(NL)/6H-SiC structures as well as the dislocation densities and the strain behaviours in the AlN epilayers has been investigated using XRD measurements. The growth times of the LT-AlN(NL) were changed to 0, 60, 120, 180, and 240 s. We observed that the mosaic structure parameters of the AlN epilayers were slightly affected by the LT-AlN(NL) growth times. However, the dislocation densities in the AlN layer are affected by the growth times of the LT-AlN(NL) layer. The highest edge dislocation density (5.48 × 10 10  ± 2.3 × 10 9  cm −2 ) was measured for the sample in which 120 s grown LT-AlN(NL) was used. On the other hand, highest screw type dislocation density (1.21 × 10 10  ± 1.7 × 10 9  cm −2 ) measured in the sample E that contains 240 s growth LT-AlN(NL). The strain calculation results show that the samples without LT-AlN(NL) suffered maximum compressive in-plane strain (−10.9 × 10 −3  ± 1.8 × 10 −4 ), which can be suppressed by increasing the LT-AlN(NL) growth times. The out-of-plane strain also has a compressive character and its values increase with LT-AlN(NL) growth times between 60 and 180 s. Same out-of-plane strain values were measured for the LT-AlN(NL) growth times of 180 and 240 s. Furthermore, the form of the biaxial stress in the AlN epilayer changed from compressive to tensile when the LT-AlN(NL) growth times were greater than 120 s.